Game theory, the science of strategy - Matos, M.; Ferreira, M. A. M. (International Journal of Latest Trends in Finance and Economics Sciences, 2014)
This paper makes a simple presentation of strategy games emphasizing their application to management in general. The language used is very straight forward and mathematical symbols are avoided.Mathematical reasoning is presented descriptively. The dominant perspective is critical in that game theory has promised so much but to a certain extent has failed to fulfill its promises, mainly in real world practice.However, recent developments envisage a brighter future for game theory in both from a practical and theoretical aspect.